Effectiveness of behaviour change techniques in lifestyle interventions for non-communicable diseases: an umbrella review - Iliatha Papachristou Nadal; Chaisiri Angkurawaranon; Ankur Singh; Yanee Choksomngam; Vidhi Sadana; Loren Kock; Apichai Wattanapisit; Nutchar Wiwatkunupakarn; Sanjay Kinra (BMC Public Health)
Abstract Objective To identify the most commonly reviewed behaviour change techniques (BCTs) and their effectiveness based on consistency across reviews for lifestyle interventions of non-communicable diseases. Design Umbrella review of systematic reviews. Data sources PubMed, Embase, PsycINFO, Cochrane CENTRAL, Global Health. Data extraction and synthesis A narrative synthesis of extracted findings was conducted. The Behaviour Change Technique v1 Taxonomy was used to identify and code behaviour change techniques (e.g., goal setting) in a standardised manner, which were independently assessed by two reviewers. Study quality was independently assessed by two reviewers using the assessment of multiple systematic review tools. Results 26 reviews were included with a total of 72 BCT labels evaluated across the different lifestyle interventions and non-communicable diseases. A total of 13 BCT clusters were identified to be reported as effective. The most commonly reviewed BCTs and their effectiveness/ineffectiveness were as follows: ‘Goals and Planning’ (12 effective/1 ineffective), ‘Feedback and monitoring’ (9 effective/3 ineffective), ‘Social support’ (9 effective/1 ineffective), ‘Shaping knowledge’ (11 effective/1 ineffective), and ‘Natural consequences’ (6 effectiveness/ 2 ineffective). The vast majority of the studies were conducted in high-income and a few in upper middle-income countries, with hardly any studies from lower middle-income and lower income studies. Conclusion The most common BCTs were ‘Goals and Planning’, ‘Feedback and Monitoring’, ‘Shaping Knowledge’, ‘Social Support’, and ‘Natural Consequence’. Based on consistency across reviews, several BCTs such as ‘Goals and Planning’, Feedback and Monitoring’, ‘Shaping Knowledge’, and ‘Social Support’ have demonstrated effectiveness (Recommendation Grade A) in improving health behaviours across a limited range of NCDs. The evidence is less clear for other BCT techniques. It is also likely that not all BCTs will be transferable across different settings. There is a need for more research in this area, especially in low-middle-income countries. Protocol registration Registered on the International Prospective Register of Systematic Reviews; PROSPERO (CRD42020222832).